Plasma medical science - Toyokuni, Shinya; Ikehara, Yuzuru; Kikkawa, Fumitaka; Hori, Masaru, 1958- (Academic Press, 2018)
Plasma Medical Science describes the progress that has been made in the field over the past five years, illustrating what readers must know to be successful. As non-thermal, atmospheric pressure plasma has been applied for a wide variety of medical fields, including wound healing, blood coagulation, and cancer therapy, this book is a timely resource on the topics discussed.